Unusual Morphologic Features of Small Duct Intrahepatic Cholangiocarcinoma with Ductal Plate Malformation - Taeudomkul , Sasathorn; Surapatpichai, Malisa; Kantasiripitak , Charinee; Laohawetwanit, Thiyaphat (Asian Medical Journal and Alternative Medicine, 2023)
We present a case of small duct intrahepatic cholangiocarcinoma with a ductal plate malformation (iCCA with DPM) showing unusual pathologic features. iCCA with DPM is an uncommon subtype of small duct iCCA. This uncommon neoplasm has unique clinicopathological characteristics. Pathological evaluation is necessary for diagnosing correctly.